Detrital zircon U–Pb age and Hf isotope constrains on the generation and reworking of Precambrian continental crust in the Cathaysia Block, South China: A synthesis - Li, X.; Li, Zheng-Xiang; Li, W. (Elsevier BV, 2014)
The South China Block, consisting of the Yangtze and the Cathaysia blocks, is one of the largest Precambrian blocks in eastern Asia. However, the early history of the Cathaysia Block is poorly understood due largely to intensive and extensive reworking by Phanerozoic polyphase orogenesis and magmatism which strongly overprinted and obscured much of the Precambrian geological record. In this paper, we use the detrital zircon U–Pb age and Hf isotope datasets as an alternative approach to delineate the early history of the Cathaysia Block. Compilation of published 4041 Precambrian detrital zircon ages from a number of (meta)sedimentary samples and river sands exhibits a broad age spectrum, with three major peaks at ~ 2485 Ma, ~ 1853 Ma and ~ 970 Ma (counting for ~ 10%, ~ 16% and ~ 24% of all analyses, respectively), and four subordinate peaks at ~ 1426 Ma, ~ 1074 Ma, ~ 780 Ma and ~ 588 Ma. Five of seven detrital zircon age peaks are broadly coincident with the crystallisation ages of ~ 1.89–1.83 Ga, ~ 1.43 Ga, ~ 1.0–0.98 Ga and ~ 0.82–0.72 Ga for known igneous rocks exposed in Cathaysia, whereas, igneous rocks with ages of ~ 2.49 Ga and ~ 0.59 Ga have not yet been found. The Hf isotopic data from 1085 detrital zircons yield Hf model ages (TDMC) between ~ 4.19 Ga and ~ 0.81 Ga, and the calculated εHf(t) values between − 40.2 and 14.4. The Archean detrital zircons are exclusively oval in shape with complicated internal textures, indicating that they were sourced by long distance transportations and strong abrasion from an exotic Archean continent. In contrast, the majority of detrital zircons in age between ~ 1.9 and ~ 0.8 Ga are euhedral to subhedral crystals, indicative of local derivation by short distance transportations from their sources. The oldest crustal basement rocks in Cathaysia were most likely formed by generation of juvenile crust and reworking of recycled Archean components in Late Paleoproterozoic at ~ 1.9–1.8 Ga, rather than in the Archean as previously speculated. Reworking and recycling of the continental crust are likely the dominant processes for the crustal evolution of Cathaysia during the Mesoproterozoic to Neoproterozoic time, with an intervenient period of significant generation of juvenile crust at ~ 1.0 Ga. Precambrian crustal evolutions of the Cathaysia Block are genetically related to the supercontinent cycles. By comparing detrital zircon data from Cathaysia with those for other continents, and integrating multiple lines of geological evidence, we interpret the Cathaysia Block as an orogenic belt located between East Antarctica, Laurentia and Australia during the assembly of supercontinent Columbia/Nuna at ~ 1.9–1.8 Ga. The Cathaysia Block amalgamated with the Yangtze Block to form the united South China Block during the Sibao Orogeny at ~ 1.0–0.89 Ga. The Laurentia–Cathaysia–Yangtze–Australia–East Antarctica connection gives the best solution to the paleo-position of Cathaysia in supercontinent Rodinia. The significant amount of ~ 0.6–0.55 Ga detrital zircons in Cathaysia and West Yangtze have exclusively high crustal incubation time of > 300 Ma, indicating crystallisation from magmas generated dominantly by crustal reworking. This detrital zircon population compares well with the similar-aged zircon populations from a number of Gondwana-derived terranes including Tethyan Himalaya, High Himalaya, Qiangtang and Indochina. The united South China–Indochina continent was likely once an integral part of Gondwanaland, connected to northern India by a “Pan-African” collisional orogen.